IgA Vasculitis following AstraZeneca/Oxford COVID-19, case report - Alzoabi , Nasser; Alqahtani, Jamal; Algamdi, Bader; Alghamdi, Nada; Ahmad, Ayesha; Alkaltham, Gaeda; Beidas , Tala; Alakloby, Omar (Acta Biomedica Atenei Parmensis, 2023)
Immunoglobulin A (IgA) vasculitis, also known as Henoch–Schönlein purpura, is an immune-mediated vasculitis that affects small vessels. IgA vasculitis could be triggered by numerous conditions including infectious and non-infectious conditions. So far, few reported cases of Covid-19 vaccines related vasculitis. We report a case of IgA vasculitis after AstraZeneca/Oxford COVID-19 vaccine. A 29-year-old healthy man who developed purpuric skin lesions one week after his second AstraZeneca/Oxford COVID-19 vaccine which complicated by glomerulonephritis and gastrointestinal involvement. Skin biopsy revealed fibrinoid necrosis and leukocytoclasia consistent with small vessel vasculitis. Due to the temporal association, AstraZeneca/Oxford COVID-19 vaccine-related IgA vasculitis would be the most likely explanation.